An evaluation of economic and education determinants on utilization of skilled delivery services by Maasai Women in Kiekonyokie sub location of Kajiado County in Kenya - Simel, Laban Lebahati; Nanduri, Lakshmi; Juma, Pamela A.; Omuga, Blasio (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternal health is one of the eight Millennium Development Goals,is central to poverty reduction and overall development efforts and it increased international attention for monitoring progress on maternal health and improving access to skilled attendants at deliveries. This research paper aimed to study economic and education determinants on the utilization of skilled delivery services by Maasai women, the study population belonging to a community of nomadic life style in North of Kajiado County in Kenya. Methods: The study design was a cross sectional descriptive study adopting both quantitative and qualitative methodologies. Results: Utilization of skilled delivery was higher among women who had a source of income (34%) compared to women who had no source of income (19%) indicating a statistical significance p=0.003. Women who had higher level of education were more likely to use skilled delivery 50% compared to 22% who had no education at all hence p=0.002. Education level had a statistical significance, (p-0.002). 69% of those who delivered in the hospital paid > 500 shillings compared to 8% of those who paid < 500 shillings. The amount paid for skilled delivery had a statistical significance, (p<0.001). 97.7% of the Maasai women in the Kajiado North study takes more than 1hour to reach to the nearest health facility while less than (1%) of them in this study takes less than 30minutes to reach to the health facility. Conclusions: In conclusion this study shows that high level of illiteracy, low economic status, distance away, cost to pay for skilled delivery hindered skilled delivery service utilization among the Maasai women.